Analisis Kebutuhan Pengembangan Media Pembelajaran Maps Digital Untuk Mengembangkan Konsep-Konsep Dasar Sejarah - Zalukhu, Muhammad Ihsan; Yefterson, Ridho Bayu (Jurnal Kronologi, 2025)
The background to this research begins with the use of learning media which has not been maximized in the learning process of students at school. This research aims to collect information to determine the need to develop a digital Map learning media to develop basic historical concepts. The research in this article uses a qualitative descriptive research method. Data collection techniques use observation and interviews, with these techniques researchers can find needs analysis from the development of Digital Maps media. The results and discussion obtained from this research are the lack of enthusiasm of students towards the learning media used in schools (conventional media). Apart from that, students are curious about digital media. Therefore, innovation is needed in the form of learning media. The learning media that can be a solution to research is the Digital Maps learning about media so that history learning is expected to be more enjoyable, and effective and learning objectives can be achieved so as to align with historical objectives.